2002
DOI: 10.1002/ajmg.10223
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in a unique family with Charcot‐Marie‐Tooth syndrome and deafness: Delineation of the clinical features and review of the literature

Abstract: Charcot-Marie-Tooth disease (CMT) is a clinically and genetically heterogeneous group of polyneuropathies characterized by degeneration of peripheral nerves, resulting in distal muscle atrophy, sensory loss, and deformities of hands and feet. We have studied 34 individuals in a large 84-member four-generation central Illinois family with autosomal dominant Charcot-Marie-Tooth and deafness. Nerve conduction velocities are consistent with type 1 CMT. Audiological evaluation revealed both auditory neuropathy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
5
42
0
Order By: Relevance
“…This phenomenon may, of course, be attributed to the time of diagnosis and symptom severity. But several reports [12,13] have documented possible anticipation in CMT and deafness, although the exact mechanism for this pattern has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may, of course, be attributed to the time of diagnosis and symptom severity. But several reports [12,13] have documented possible anticipation in CMT and deafness, although the exact mechanism for this pattern has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when subjects were profoundly deaf, all DPOAEs were lost, a feature of a profound sensory and neural hearing loss. Affected family members do not have any evidence of peripheral and/or cranial nerve involvement and are distinguished from other forms of hereditary AN occurring with peripheral neuropathies (Butinar et al 1999;Kalaydjieva et al 2000;Kovach et al 2002;Starr et al 2003), Refsum's disease (Oysu et al 2001), and Friedreich's ataxia (Satya-Murti et al 1980) or other cranial neuropathies (Ceranic and Luxon 2004). In the peripheral myelin protein 22 (PMP22) form of AN (Kovach et al 2002;Sambuughin et al 2003), subjects may also have impaired outer hair cell functions (absent OAEs), resulting in a sensorineural phenotype similar to some affected family members in the present report.…”
Section: Phenotypes Of Deafnessmentioning
confidence: 99%
“…The investigation of affected family members with inherited forms of AN can provide a longitudinal view of the natural history of symptoms and findings in this disorder. For instance, several inherited forms of AN have now been described in association with peripheral neuropathies (Butinar et al 1999;Kalaydjieva et al 2000;Kovach et al 2002;Starr et al 2003), Refsum's disease (Oysu et al 2001), Friedreich's ataxia (Satya-Murti et al 1980) and also in families without peripheral neuropathies accompanying mutations of the otoferlin (OTOF) gene (Yasunaga et al 1999;Varga et al 2003) and mitochondria (Merchant et al 2001;Zwirner et al 2001). Both the age of onset and the rate of progression vary in these different genetic forms of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused attention on auditory function in CMT by identifying hearing disorder as a prominent feature in several distinct genetic variants including primary demyelinating forms (CMT1) due to mutation of PMP22 gene duplication (Boerkoel et al, 2002;Kovach et al, 2002;Hattori et al, 2003;Joo et al, 2004), primary axonal forms (CMT2) due to mutations of MPZ gene (Chapon et al, 1999;De Jonghe et al, 1999;Misu et al, 2000;Hattori et al, 2003;Starr et al, 2003), connexin 31 (GJB3) gene (Lopez-Bigas et al, 2001), Connexin 32 (Cx32) gene (Boerkoel et al, 2002;Hattori et al, 2003), and in a mixed demyelinating/axonal autosomal recessive motor-sensory neuropathy, HMSN-Lom, particular to Roma populations due to a mutation of the NDRG1 gene (Kalaydjieva et al, 1998;Butinar et al, 1999;Kalaydjieva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…At least three of these studies (Butinar et al, 1999;Kovach et al, 2002;Starr et al, 2003) demonstrated that affected individuals showed normal physiological measures of cochlear outer hair cell activity (otoacoustic emissions, OAEs) but abnormal auditory nerve activity (auditory brainstem responses, ABRs), localizing the hearing loss to dysfunction of the auditory nerve. Pathological examination of the cochlea in one MPZ patient with deafness showed marked loss of both auditory ganglion cells and nerve fibers with normal numbers of inner hair cells and near normal numbers of outer hair cells (Starr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%